Strategi Komunikasi Prokopim Kota Bandung melalui Akun Instagram - Dhea Syahranie Putri; Riza Hernawati (Bandung Conference Series: Public Relations, 2023)
Abstract. Content is an important part of the management of social media, so the content needs to be packed with interesting innovations, as it is carried out by the Bandung government's instagram account that keeps "Baban Ndung Juju Ara" episode of "Jatanras" content as a form of communication strategy. The study was done to learn about the communication strategy for Bandung prokopim through the instagram account applied to content "Baban Ndung Juju Ara" episode "Jatanras" by using qualitative methods for a case study approach. Data collection techniques involve interviews, observations, documentation, and literature studies. Data analysis techniques use data reduction, data presentation and data verification. To test the validity of data, the research used source triangulation. The theories used in the study are communications strategy theories, message creation models, new media theory, and government communications. Results in research showing showing a positive episode theme from five important stages of monitoring issues, setting agendas, urgency of messages, themes, and content packaging. Further in the process of creating messages is done through theme selection, the selection of messages to be delivered and the packaging of the messages. In the manufacture of content, there are seven stages involving processing issues, photocopying messages, coordination meetings, script and storyboards, filming, editing, reporting through the group, and posting on social media. Using informal language had the goal of reflecting the identity of the people of Bandung, and the techniques of approaching people. Abstrak. Konten merupakan satu hal yang penting dalam pengelolaan sebuah media sosial sehingga konten perlu dikemas dengan inovasi yang menarik Hal ini juga dilakukan oleh Prokopim Kota Bandung selaku pengelola akun Instagram milik pemerintah Kota Bandung yang membuat konten “Baban Ndung Juju Ara” episode “Jatanras” sebagai bentuk strategi komunikasi. Penelitian ini dilakukan untuk mengetahui strategi komunikasi Prokopim Kota Bandung melalui akun Instagram yang diterapkan pada konten “Baban Ndung Juju Ara” episode “Jatanras” dengan menggunakan metode kualitatif pendekatan studi kasus. Teknik pengumpulan data dilakukan dengan wawancara, observasi, dokumentasi, dan studi kepustakaan. Teknik analisis data menggunakan reduksi data, penyajian data serta verifikasi data. Untuk menguji keabsahan data, penelitian ini menggunakan triangulasi sumber. Teori yang digunakan dalam penelitian ini yakni teori strategi komunikasi, model penyusunan pesan, new media theory, serta komunikasi pemerintah. Hasil dalam penelitian memperlihatkan penentuan tema episode melalui lima tahapan penting meliputi monitoring isu, agenda setting, penentuan urgensi pesan, penentuan tema, dan penentuan pengemasan konten. Selanjutnya dalam proses penyusunan pesan dilakukan melalui pemilihan tema, pemilihan pesan yang ingin disampaikan dan pengemasan pesan. Dalam pembuatan konten, terdapat tujuh tahapan meliputi pengolahan isu, penyusunan pesan, rapat koordinasi, pembuatan script dan storyboard, syuting, editing, pelaporan melalui grup, dan memposting di media sosial. Penggunaan bahasa informal memiliki tujuan yaknimencerminkan identitas masyarakat Kota Bandung, dan teknik pendekatan dengan masyarakat.